CONCEPT OF SOPHA (INFLAMMATION): A CRITICAL STUDY - Panda, Ashok; Tripathy, Rabinarayan (International Journal of Research -GRANTHAALAYAH, 2020)
Back ground- Inflammation has a decisive role in pathological classification of diseases in modern medicine and well-known phenomenon of infectious diseases and Non communicable disorders (NCD) also. Ayurveda emphasised the doshic involvement in pathophysiology of diseases process and the phenomenon of Sopha is undetermined in diagnosis and treatment. Objective- A literature survey from Ayurveda classical texts was undertaken to understand the role of Sopha in disease process. Methods- The enumerations of Sopha in Bruhatrayee, Madhav nidana & Bhela Samhita are critically studied to find out its etiology, types, pathogenesis and line of treatment. Enumeration- Sopha is very fundamental to understand the disease process in Ayurveda. The normal snigdha-sheet- agneya character of Srotas get disturbed by the Vidahi & Abhisandhya dravyas, as a result there is a disturbed in the transport mechanism of the affected Srotas. Sopha can be a symptom of any disease and/or an independent disease and may be a complication of other diseases. Sopha can be classified as Antah Sopha & Bahir Sopha. Discussion- The concept of sopha was discussed in terms of pathology and treatment of modern science. Conclusion- Sopha is linked with wide spectrum of Infectious as well as Non communicable disorders (NCD). This study also found out a range of therapies for Sopha driven diseases. It can be recommended to include this concept of Sopha in Ayurveda undergraduate and post graduate curriculum.